Removal of hydrogen sulphide and odour from tannery & textile effluents. (2020) - Shivasankaran, N.; Balan, A.V.; Sankar, S.P.; Magibalan, S.; Dinesh, C.M.
Abstract: Leather and textile effluents consist of highly toxic organic, inorganic substances and heavy metals. It releases malodorous gaseous pollutants such as Hydrogen Sulphide (H2 S), Carbon dioxide, Methane and other traceable elements during treatment processes. Among these gases, H2 S is toxic, irritable, and flammable gas that causes health effects when exposed to even lower concentrations. This paper deals with the removal of H2 S and eliminating the foul odour from the wastewater collection by adding oxidation chemicals such as NaOCl, H2 O2, O3 and Sulpha sponge. The sulpha sponge and ozonation processes were found to be very effective in treating these effluents respectively.